Simplified Hepatitis C Virus Genotyping by Heteroduplex Mobility Analysis - White, Peter A. (American Society for Microbiology, 2000)
Heteroduplex mobility analysis (HMA) was used to genotype hepatitis C viruses (HCV) with PCR fragments derived from the 5′ untranslated region (5′-UTR) or the NS5b region. HCV 5′-UTR fragments were amplified from 296 serum samples by use of a combined reverse transcription-PCR assay, and the genotypes of isolates were determined by sequencing. HCV genotype distributions in Australia were 39% for genotype 1a, 15% for 1b, 3% for 1a/b, <1% for 2a/c, 5% for 2b, 34% for 3a, <1% for 3b, and 1% for 4, and 1% of patients were infected with more than one genotype. Pairwise HMA of subtypes 1a, 1b, 2a/c, 2b, 3a, 3b, 4a, and 6a demonstrated that five distinct heteroduplex patterns were formed between the eight subtypes. A reference panel that contained a representative of each pattern (1a, 2b, 3a, 4a, and 6a) was used for genotyping. The pattern of heteroduplexes formed when a test isolate was mixed with the five reference isolates was correlated with the genotype, as determined by sequencing. Genotypes determined by HMA correlated exactly with sequencing results within the groups 1, 2, 3a, 3b/4, and 6. HMA was also used to simplify the identification of mixed infection with two HCV genotypes. In further studies, with amplicons from the NS5b region, HMA classified isolates into their respective subtypes, and the heteroduplex mobility ratio correlated closely with nucleotide sequence variation at the isolate, subtype, and genotype levels. HMA provides an adaptable, inexpensive, and rapid method of genotyping HCV that requires fewer resources than DNA sequencing.